Assessment of nematode and microbial diversity and screening of entomopathogens in revegetated post-coal-mining land in Kutai Kartanegara District, East Kalimantan, Indonesia - SOPIALENA SOPIALENA; ROSFIANSYAH ROSFIANSYAH; ANDI SURYADI (Biodiversitas Journal of Biological Diversity, 2024)
Abstract. Sopialena, Rosfiansyah, Suryadi A. 2024. Assessment of nematode and microbial diversity and screening of entomopathogens in revegetated post-coal-mining land in Kutai Kartanegara District, East Kalimantan, Indonesia. Biodiversitas 25: 2921-2930. Post-coal-mining management should strive toward site revegetation. The success of such revegetation efforts is largely determined by the soil's fertility status, which encompasses physical, chemical, and biological components. Biological fertility is indicated by the presence and abundance of soil microbes and nematodes. The objective of this study was to identify the diversity of nematodes and soil microbes in ex-coal-mining land revegetated with oil palm in Kutai Kartanegara District (East Kalimantan, Indonesia), to screen for entomopathogenic nematodes and microbes, and to analyze their relationships with the chemical fertility status of the land. As a control, non-mining land was also investigated. The results showed that microbial diversity and density (including fungi and bacteria) in the ex-coal-mining area were significantly lower compared to the control. Additionally, a decrease in microbial diversity and density was found in deeper soil layers of both post-mining and non-mining lands. In contrast, soil nematodes were more abundant in post-mining land, both in terms of diversity and density, and were also more plentiful in the deeper soil layers. Among the nematodes and microbes studied, only Heterorhabditis and Steinernema (nematodes), Trichoderma (fungi), and Bacillaceae (bacteria) were identified as entomopathogens, causing death in Tenebrio molitor L. larvae. Overall, soil fertility in ex-coal-mining land was observed to be lower, characterized by decreased soil pH, basic saturation, Soil Organic Carbon (SOC), and nutrient content, which contributed to a reduced microbial community compared to non-mining land.